The Development of backhand Drive Stroke Technique Training in Audiovisual Based for Beginner Badminton Athletes - Adiluhung, Rezza; Kristiyanto, Agus; Kunta, Sapta (Quality in Sport, 2020)
This research aimed to afford the backhand drive stroke technique training in audiovisual based for beginner category badminton athletes. This development research was referred to the development model that has been done by Borg & Gall and has been modified by Sugiyono into two steps, there were pre-development step and development step. The large scale testing was consisted of ten beginner category badminton athletes of PMS Surakarta. The effectiveness testing was done to 25 beginner category badminton athletes of PMS Surakarta by using pre-experiment Intact-Group Comparison, the groups were divided into two in order to make one group would be given a treatment, other group would be a control group. The result of the research showed that the group which was given backhand drive stroke technique training based on audiovisual treatment had higher scores than the control group.